Pengaruh Citra Merek dan Label terhadap Minat Beli (Studi Kasus Mie Gacoan di Kota Bandung) - Rahmah, Diefta Agniyya; Hasbi, Imanuddin (Jurnal Samudra Ekonomi dan Bisnis, 2023)
Mie Gacoan is one of the spicy noodle restaurants spread across the city of Bandung. Bandung itself is a city known as a culinary paradise. With these conditions, competitors are currently emerging. Mie gacoan therefore needs to improve its marketing to attract purchase intention. The research aim is to analyze how brand image and labels influence increasing customer purchase intention in Mie Gacoan products. This quantitative descriptive research uses multiple linear regression methods to analyze data. Data was obtained through distribution to 110 respondents. Partial test results show that brand or label image has a significant partial influence on purchase intention. Apart from that, the results of simultaneous testing show that brand image and labels together have a significant effect on purchase intention. Thus, it is recommended that Mie Gacoan managers develop labels and brand images in an effort to increase purchase intention.